The Role of Ecological and Digital Leadership in Improving School Performance - Fitriana, Nita; Zuraida, Lukia (Journal of Regional Economics and Development, 2025)
The advancement of technology and environmental issues has become a major challenge in the education sector. Schools are required to adopt digital transformation while simultaneously implementing sustainability principles. This study analyzes the role of ecological leadership and digital leadership in improving the performance of Sekolah Cendekia BAZNAS (SCB). This research employs a qualitative case study approach, collecting data through observations, in-depth interviews, and document analysis. The findings reveal that ecological leadership at SCB is manifested in environmental policies, innovative programs such as the "Kebun Sehat" and Biofloc fish farming, as well as active participation in the Adiwiyata Program. Meanwhile, digital leadership is reflected in the utilization of technology for communication, digital learning, and data-driven school management. The implementation of these leadership styles has led to improvements in school accreditation, student achievements, and overall educational management effectiveness. This study implies that the synergy between ecological and digital leadership can serve as a strategic leadership model in modern education, focusing not only on academic excellence but also on fostering environmental awareness and digital literacy within the school community.